The Gendered Consequences of Financial Crises: A Cross-National Analysis. Issue 4 (December 2019) - Blanton, Robert; Blanton, Shannon; Peksen, Dursun
Abstract : What effects do financial crises have on women's well-being? While much research has addressed various socio-economic and political consequences of financial crises, the gendered impact of financial crises are empirically underexplored. Moreover, extant literature has mainly focused on specific crises or countries with little attempt at determining possible common effects and patterns across the world. To provide broader insight into the gendered consequences of financial crises, we examined the degree to which five types of financial crises—banking crises, currency crises, domestic sovereign debt crises, external sovereign debt crises, and inflation crises—affect women's health and educational outcomes as well as their participation in the formal economy and politics. We also examined the persistence of these effects in the postcrisis years. The results from a panel of 68 countries for the years 1980 to 2010 indicate that financial crises undermine women's participation in the formal workforce, their presence in politics, their educational attainment, and their health outcomes. We also found significant lingering effects of financial crises: the deleterious gendered effects of crises persist even seven years after the end of a crisis.